Efficacy of different types of aerobic exercise in fibromyalgia syndrome: a systematic review and meta-analysis of randomised controlled trials - Häuser, Winfried; Klose, Petra; Langhorst, Jost; Moradi, Babak; Steinbach, Mario-Peter; Schiltenwolf, Marcus; Busch, Angela (Arthritis Research & Therapy, 2010)
The efficacy and the optimal type and volume of aerobic exercise (AE) in fibromyalgia syndrome (FMS) are not established. We therefore assessed the efficacy of different types and volumes of AE in FMS.
Gesehen am 15.06.2023